Penggunaan Multimedia Interaktif (MMI) Sebagai Media Pembelajaran Dalam Meningkatkan Prestasi Belajar Fisika - Ana Silfiani Rahmawati; Rahmawati P. Dewi (Department of Physics Education, Universitas Mataram, 2019)
The purpose of this study was to determine the use of interactive multimedia as a learning medium in improving physics learning achievement. This type of research is an experimental design one group pre-test post-test with a quantitative approach. The population in the study were all students of class X semester 2 of SMK Negeri 2 Ende which consisted of 13 classes in 5 skill programs totaling 421 people and the sample of the research was 26 students of TKJ class XC as many as 26 people. The sampling technique was purposive sampling. Data collection techniques in this study are achievement test techniques. Data were analyzed by t test. The results showed that the use of interactive multimedia (MMI) as a learning medium can improve physics learning achievement. This is evidenced by the value of t count ÃÆ t table or 3.491> 1.708 with the degree of freedom to list the distribution t is dk = N-1 = 26-1 = 25, and the significance level is 0.05.